#19 Chemically modified xanthan gum as a potential carrier for a model drug Lornoxicam - Murtale, Sandip (Journal of Pharmaceutical Chemistry, 2022)
This study investigated the utility of chemically modified xanthan gum (XG) for controlled drug delivery of Lornoxicam. Lornoxicam belongs to an oxicam class of nonsteroidal anti-inflammatory drugs. It inhibits the cyclooxygenase enzyme and thereby interferes with prostaglandins synthesis. Chemical modification of xanthan gum was carried out by using a thiol-esterification reaction employing thioglycolic acid (TGA) in the presence of a catalytic amount of hydrochloric acid. The reaction mixture was refluxed at 800 °C for 2.5 h. The above reaction mixture was cooled and precipitated by the addition of methanol. Microwave irradiated thiolated xanthan gum was also prepared by further irradiation of thiolated xanthan gum by microwave using 750 W frequency. The morphological characteristics, functional group, and thermal behavior of grafted gum were evaluated using SEM, FT-IR, XRD, and DSC. The controlled release applications of thiolated and microwave irradiated xanthan gum were comparatively evaluated with crude xanthan polymer by formulating tablets containing Lornoxicam as a model drug. Swelling and in vitro drug release behavior were also investigated. The results of FT-IR, DSC, and X-ray diffraction studies confirm that grafting was obtained. FT-IR study showed that in thiolated xanthan gum and microwave irradiated gum, additional peaks were observed, those which were not present previously in crude xanthan gum. The bands closer to 2568.00 cm−1 and 2584.70 cm−1 reflect the presence of SH stretch of the thiol group. Sustained-release tablets of Lornoxicam were prepared by direct compression technique using crude, thiolated, and microwave irradiated xanthan gum. The physical properties of compressed tablets like thickness, hardness, weight variation, and friability complied with the official limits. Free-flowing powder facilitates the formation of tablets with ideal properties. The swelling index of modified xanthan gum was high compared to native xanthan gum. In vitro release study conducted using phosphate buffer (pH 6.8) revealed a sustained release profile (24 h) of Lornoxicam from thiolated and irradiated xanthan gum as compared to crude xanthan. Thiolation and irradiated xanthan gum sustained the release of Lornoxicam over a prolonged period and could be a promising Lornoxicam carrier in oral delivery to enhance antinociceptive and anti-inflammatory efficiency.